2023
DOI: 10.1039/d3cc04278b
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon enabled Claisen rearrangement with sunlight

Radha Krishna Kashyap,
Shreya Tyagi,
Pramod P. Pillai

Abstract: Plasmonic-heat generated from the solar irradiation of gold nanoparticles is used as the thermal energy source for the Claisen rearrangement of allyl phenyl ether to 2-allylphenol, which is conventionally performed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…This presents a potential challenge for organic reactions which are typically run dilute or require certain low-boiling solvents to work, as contact with the nanoparticle and effective heat transfer may become difficult. However, the Pillai group demonstrated that photothermal agents could function in a system without direct interaction between nanoparticle and substrate (Figure a) . Their 2023 report used a specialty reactor that isolated plasmonic gold nanoparticles from allyl phenyl ether to exempt any competitive plasmonic effects in their system.…”
Section: Couplings Rearrangements and Diels–alder Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents a potential challenge for organic reactions which are typically run dilute or require certain low-boiling solvents to work, as contact with the nanoparticle and effective heat transfer may become difficult. However, the Pillai group demonstrated that photothermal agents could function in a system without direct interaction between nanoparticle and substrate (Figure a) . Their 2023 report used a specialty reactor that isolated plasmonic gold nanoparticles from allyl phenyl ether to exempt any competitive plasmonic effects in their system.…”
Section: Couplings Rearrangements and Diels–alder Reactionsmentioning
confidence: 99%
“…However, the Pillai group demonstrated that photothermal agents could function in a system without direct interaction between nanoparticle and substrate (Figure 10a). 57 Their 2023 report used a specialty reactor that isolated plasmonic gold nanoparticles from allyl phenyl ether to exempt any competitive plasmonic effects in their system. Using this reactor and focused sunlight, they achieved a highly efficient Claisen rearrangement.…”
Section: Couplings Rearrangements and Diels−alder Reactionsmentioning
confidence: 99%